Antibacterial Activity of Piper betle Linn Extract Against Vibrio parahaemolyticus Causes of Disease in Vaname Shrimp (Litopenaeus vannamei) - Harlina, Harlina; Ibrahim, Azizah; Hamdillah, Andi; Ilmiah, Ilmiah (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2024)
Betel leaf (Piper betle L.) is a medicinal plant that has antibacterial properties. Betel leaves contain various chemical ingredients, including essential oils, phenols, terpenoids, tannins, polyphenols and steroids. This study aims to determine the inhibitory power of betel leaf extract (Piper betle L) on the growth of Vibrio parahaemolyticus which causes disease in vaname shrimp (Litopenaeus vannamei) and determine the minimum concentration of betel leaf extract that can inhibit growth and the minimum concentration that can kill V. parahaemolyticus internally. vitro. This research was carried out at the Integrated Biology Laboratory, Faculty of Fisheries and Marine Sciences, Indonesian Muslim University. A total of 500 g of betel leaf was extracted using the maceration method to produce 39.90 g of thick extract. Next, various concentrations of betel leaf extract were tested for their antibacterial effect on the growth of V. parahaemolyticus using the double layer method. The results of this research show that betel leaf extract is able to inhibit the growth of the bacteria V.parahaemolyticus. The minimum inhibitor concentration (MIC) value is at a concentration of 0.78 mg/mL and the maximum bactericidal concentration (MBC) at a concentration of 1.56 mg/mL, so it can be concluded that sirh leaf extract (Piper betle L) has the potential to be developed as an antibacterial for V. parahaemolyticus.